PEMODELAN MENGGUNAKAN STRUCTURAL EQUATION MODELING (SEM) UNTUK MENGETAHUI PENGARUH KUALITAS LAYANAN DAN KEUNGGULAN PRODUK TERHADAP KEPUASAN DAN KEPERCAYAAN SERTA LOYALITAS PELANGGAN - Heri Irawan; M. Thaib Hasan (Jurnal Teknologi, 2021)
The purpose of this study is to examine the effect of service quality, product superiority on customer satisfaction and customer trust on the effect on increasing customer loyalty. Using these variables, which are caused by the results of research before Parasuraman, Zeithaml and Berry, (1985; 1988; 1990 and 1994); Fornell, (1992); Anderson et al., (1994); and Thamrin, (2003), found a direct influence of service quality and product superiority on customer satisfaction and customer trust in the effect of increasing customer loyalty. The use of these variables is able to solve problems that arise in UNSAM, for which the customer is not satisfied. The sample of this study were 100 UNSAM customers. Structural Equation Modeling (SEM) is run by AMOS 16 software for data analysis. The analysis shows that service quality and product excellence have a significant positive effect on customer satisfaction and customer trust. customer satisfaction has a significant positive effect on repurchases. These empirical results indicate that to increase customer loyalty as a cause of customer dissatisfaction by UNSAM must focus on factors such as: service quality, product excellence, customer satisfaction and customer trust due to factors that have proven to have an influence on the level of customer loyalty. The theoretical implications and suggestions for future research have been outlined at the end of this study.